Turbulence intensity behavior in several wind tunnel cross-sectional areas - Richmond-Navarro, Gustavo (2023)
Considering that more and more wind turbines operate at high turbulent flows, a study of the turbulence intensity (TI) in several wind tunnel cross-sectional areas was done in this paper. A wind tunnel with a test section 15 m long, 3.6 m wide and 2 m high was used; a wooden grid was placed to generate turbulence and the wind velocity was measured with a hot wire anemometer. To determine if there are significant variations of the TI value, five points (center, up, down, left, and right) at four tunnel cross-sections downstream from the grid were measured. It was determined that the TI varies drastically within the area. An error rate from 3.6 % up to 15.2 % occurred if the TI is considered only at the cross-sectional axis; to truly describe the turbulent flow it is necessary to use the average of the measurements taken in the cross-sectional area.